2017
DOI: 10.1002/cmdc.201700063
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Features of the YAP Inhibitor Verteporfin: Synthesis of Hexasubstituted Dipyrrins as Potential Inhibitors of YAP/TAZ, the Downstream Effectors of the Hippo Pathway

Abstract: Porphyrin derivatives, in particular verteporfin (VP), a photosensitizer initially designed for cancer therapy, have been identified as inhibitors of the YAP–TEAD interaction and transcriptional activity. Herein we report the efficient convergent synthesis of the dipyrrin half of protoporphyrin IX dimethyl ester (PPIX‐DME), in which the sensitive vinyl group was created at the final stage by a dehydroiodination reaction. Two other dipyrrin derivatives were synthesized, including dipyrrin 19 [(Z)‐2‐((3,5‐dimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 33 publications
(56 reference statements)
3
51
0
Order By: Relevance
“…Having demonstrated that blocking SPHK1 activity attenuates BLM-or TGF-β-mediated mtROS and the expression of FN and α-SMA, we investigated the effect of YAP1 inhibition, or the downregulation of YAP1, with shRNA on mtROS, FN, and α-SMA expression in lung fibroblasts. The HLFs were pre-treated with YAP1 inhibitor verteporfin (1 µ M) [45,46] for 1 h prior to the TGF-β (5 ng/mL) challenge for 3 h, and mtROS was determined by MitoSOX. The inhibition of YAP1 by verteporfin reduced the TGF-β-induced mtROS ( Figure 8A), suggesting a role for YAP1 in mtROS production.…”
Section: Inhibition or Downregulation Of Yap1 Reduces Tgf-β-induced Mmentioning
confidence: 99%
“…Having demonstrated that blocking SPHK1 activity attenuates BLM-or TGF-β-mediated mtROS and the expression of FN and α-SMA, we investigated the effect of YAP1 inhibition, or the downregulation of YAP1, with shRNA on mtROS, FN, and α-SMA expression in lung fibroblasts. The HLFs were pre-treated with YAP1 inhibitor verteporfin (1 µ M) [45,46] for 1 h prior to the TGF-β (5 ng/mL) challenge for 3 h, and mtROS was determined by MitoSOX. The inhibition of YAP1 by verteporfin reduced the TGF-β-induced mtROS ( Figure 8A), suggesting a role for YAP1 in mtROS production.…”
Section: Inhibition or Downregulation Of Yap1 Reduces Tgf-β-induced Mmentioning
confidence: 99%
“…Verteporfin, a member of porphyrin family, is identified as the most effective inhibitory drug against YAP1-TEADs complex, and it is approved by Food and Drug Administration (FDA) for the treatment of macular degeneration. 5,96 Inhibition of YAP1 by genetic silencing or verteporfin can increase the sensitivity of cisplatin, erlotinib and gefitinib in different cancer types. 13,16,18,86 In addition to verteporfin, other drugs such as dasatinib and statins are capable of blocking YAP1/TAZ activities through the suppression of YAP1/TAZ associated components.…”
Section: Yap1 Signaling and Drug Resistancementioning
confidence: 99%
“…However, verteporfin’s promise as a YAP/TAZ-TEAD inhibitor is outweighed by high toxicity and the accounts of YAP/TAZ-TEAD independent effects [ 196 , 197 , 198 ]. Although verteporfin prevents YAP-TEAD activity by preventing YAP-TEAD interaction [ 104 ], other evidence shows it can also activate the Hippo pathway [ 191 ], and regulate YAP and TAZ protein expression [ 189 , 190 , 191 , 195 , 199 ]. This apparent lack of specificity further diminishes its therapeutic potential.…”
Section: Therapeutic Potential Of Targeting Yap/taz-tead In Cancermentioning
confidence: 99%